A alienação fiduciária de bem imóvel em garantia de obrigações em geral e a proteção do bem de família - Cardins, Rafaella Mayana Alves Almeida (2017)
The fiduciary alienation in warranty of real estate and the Real Estate Financing System were introduced in the Brazilian juridical system by Law n° 9.514/97. Since then the possibility of the constitution of a fiduciary property of real estate has been discussed as a lien on the property which is not linked to the Real Estate Financing System. When Law n° 10.931/2004 was passed those discussions were intensified for its 51st article has established the fiduciary alienation of real estate as a valid warranty amongst other warranties in general, which are still valid to this day. When taking into consideration the legal applicability of the fiduciary alienation as a general warranty mechanism (out of the Real Estate Financing System) a problem arises: how does the Homestead holds against the fiduciary alienation in warranty of real estate? Considering such proposition, we analyze initially the aspects which characterize the fiduciary alienation in warranty of real estate; subsequently the fiduciary alienation in warranty of real estate as a general and a specific mechanism of the Real Estate Financing System; lastly we study the aspects related to the protection of the Homestead against the possibility of the establishment of a fiduciary property that exceeds the purposes of the Real Estate Financing System. To implement this quantitative research a deductive approach method has been used along with a bibliographical and documental research. It is concluded that the only property permanently used as a residence of a family entity is alienable and, this way, the owner of his property can sell it fiducially for the purpose of ensuring compliance with obligations related to the Real Estate Financing System or not. In case of defaulting, the trustor debtor will not enjoy the protection related to the immovable asset provided for by Law nº 8.009 /1990, since he no longer owns the property. However, the movable assets that holds the property, on which he holds the possession, will be protected by the family homestead.